Ductility considerations in seismic design of reinforced concrete building - Elawady, Mahmoud Helal Saadeldin (2017)
This study is conducted to review the methods proposed by European national seismic codes in order to incorporate the concept of ductility of structural elements. In order to assess how to take in account the ductility class of a reinforced concrete building which is prescribed in Eurocode 8 and its influence in the structural design of the building, the structures are analysed with Sap2000 software for their responses to lateral loading by applying the static non linear push-over analysis. These structures are assumed to be located in different seismic hazard zones (Low, Medium and High hazard) in the mainland of Portugal, subjected to horizontal loads deducted from the European seismic code and designed using Eurocode 8. There a strict recommendation from the European seismic code (Eurocode 8) (EN 1998-1, 2004), to consider one of three ductility classes mentioned in Eurocode 8, ductility class low DC L, ductility class medium DC M, and ductility class high DC H, Eurocode 8 explaines in details the rules to design the structure for the the three ductility class, however it is not clear for the designer to select the suitable ductility class for the structure to have achieve the highest performance of building structure during the earthquake with less damages and economic cost. Nonlinear pushover static analysis, used to assess the design of the frames for three ductility classes in different seismic zones, the assessment results show that, Ducility class medium DC M, have a high performance near to Ductility class high DC H, even in the high hazard seismic zones, and the costs for DC M are close for DC H, could be less, if the workmanship is included, because DC H will cost more for the workmanship according to its complexity of the detailing.